Evaluation of the performance of the National Tuberculosis Program of Liberia during the 2014–2015 Ebola outbreak - Desta, Kassaye Tekie (BMC Public Health, 2019)
BACKGROUND: Liberia is among the three west African countries which were crippled by the Ebola Virus Disease (EVD) outbreak of 2014. One of the programs which was affected by the EVD outbreak was the National Leprosy and Tuberculosis Control Program (NLTCP). Determining the magnitude of the impact of EVD on the NLTCP performance is crucial in restoring the service and in devising effective post EVD strategies. The purpose of the study was to analyse the impact of EVD outbreak on the performance of the NLTCP of the Ministry of Health (MOH) OF Liberia. METHODS: A cross sectional study design was conducted in 2016 using both quantitative and qualitative methods. Quantitative data was used for the Tuberculosis (TB) program evaluation before EVD (2012–2013) and during EVD (2014–2015). Qualitative data was used to complement the data obtained for the quantitative study. Descriptive statistical analyses of quantitative data were conducted using Microsoft Excel. RESULTS: Notified TB cases of all forms decreased from 7822 in 2013 to 4763 and 6118 in 2014 and 2015 respectively. The number increased to 7180 and 7728 in 2016 and 2017 respectively. The TB treatment success rate was 71 and 61% in 2014 and 2015 respectively compared to the 83% in 2013. The treatment success rate was 77% in 2016. The loss to follow up (LTFU) was as high as 47% in some regions which were highly affected by the EVD outbreak. The national average LTFU was 5–10% in 2012–2013 and 16 and 21% in 2014 and 2015 respectively. The percentage of TB patients with known HIV result decreased from 75% in 2013 to 74 and 42% in 2014 and 2015 respectively. TB culture and drug susceptibility testing service was interrupted throughout the outbreak. The results of the focal group discussions and interviews conducted in our study also indicated that the TB case finding and the TB treatment outcome was significantly affected by the EVD outbreak. CONCLUSION: Notified TB cases and treatment outcome was significantly affected by the EVD outbreak which occurred in 2014 and 2015 in Liberia. Effective restoration strategies should be developed in order to improve the TB case finding and treatment outcome.